Floorsys wins gold medal in 16th KIK UA - Nor Salwana, Mohammad Idris (2022)
JOHOR, 4 October 2022 - The FLOORSYS Group from the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang (UMP) won the gold medal in the 16th Public University Innovative and Creative Group (KIK) Convention held at Universiti Tun Hussien Onn Malaysia (UTHM) recently.